2022
DOI: 10.3389/fnins.2022.1034547
|View full text |Cite
|
Sign up to set email alerts
|

Slow, deep breathing intervention improved symptoms and altered rectal sensitivity in patients with constipation-predominant irritable bowel syndrome

Abstract: Background and aimLimited treatment options have been shown to alter the natural course of irritable bowel syndrome (IBS). Slow, deep breathing (SDB) is a common pain self-management intervention. This pilot study aimed to explore the impact of SDB on measures of autonomic and anorectal functions as well as patient-reported symptoms in constipation-predominant IBS (IBS-C).MethodsEighty-five IBS-C patients were enrolled in this study and randomly assigned to the experimental group (Group A, n = 42) and the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Out of the four studies that were conducted, only two found a statistically significant improvement in symptoms for the group of participants who partook in the HRV biofeedback intervention (Stern, Guiles, and Gevirtz 2014;Liu et al 2022). Out of the four studies, only two of them employed the use of a control group as a comparison for the biofeedback groups results (Liu et al 2022;Jurek et al 2022), while the other two did not employ a control or similar method (Stern, Guiles, and Gevirtz 2014;Ebert 2012). The studies that did use a control group found no statistically significant difference in any measurement.…”
Section: Interventional and Control Group Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Out of the four studies that were conducted, only two found a statistically significant improvement in symptoms for the group of participants who partook in the HRV biofeedback intervention (Stern, Guiles, and Gevirtz 2014;Liu et al 2022). Out of the four studies, only two of them employed the use of a control group as a comparison for the biofeedback groups results (Liu et al 2022;Jurek et al 2022), while the other two did not employ a control or similar method (Stern, Guiles, and Gevirtz 2014;Ebert 2012). The studies that did use a control group found no statistically significant difference in any measurement.…”
Section: Interventional and Control Group Resultsmentioning
confidence: 99%
“…Of the two studies that included a control group (Liu et al and Jurek et al) within their protocol, both found no significant changes in the IBS-SSS sores over the study, compared to baseline. One of the studies (Liu et al 2022) found a trend that could be indicative of such a period of time to find efficacy. Within their study, they completed follow ups at weeks three and six after the commencement of the slow, deep breathing exercise (SDB).…”
Section: Gastrointestinal Outcome Measuresmentioning
confidence: 99%
See 3 more Smart Citations